Geographies of relational coordination in venture capital firms - Andreas Kuebart (European Planning Studies, 2019)
Venture capital (VC) firms are crucial actors in entrepreneurial ecosystems. Through the development towards a digital economy, they have gained further relevance, which caused the VC industry to diversify in terms of business models. This article offers a new heuristic to study the VC industry by developing a classification of VC firms. By drawing on a framework of different dimensions of relational distance in investment relations, different types of relational coordination are identified by comparing VC firms in Germany. The types of VC business models are found to produce relational geographies of investing as they relate with their portfolio startups in different ways. A relational perspective on VC thus provides the opportunity to step beyond pure territorial approaches on VC.
Keywords: 710; Venture capital; relational distance